PATIENT SATISFACTION: A COMP ARI SON BETWEEN GOVERNMENT AND PRIVATE CLINICS IN MUKIM LABU, SEPANG, SELANGOR - Yunus MA; Nasir MMT; Nor Afiah MZ; Sherina MS; Faizah MZ (Malaysian Journal of Public Health Medicine, 2004)
A cross sectional study was carried out to identify and compare factors that contribute to patient satisfaction towards the medical care services provided at the outpatient clinic in government health clinics and private clinics in Mukim Labu, SeJJang, Selangor. Systematic sampling for government clinic and universal sampling for private clinics were done and data was collected via face-to-face interview based on a validated Patient Satisfaction Questionnaire (PSQ). A total of 181 patients aged 15 to 75 years old were selected, comprising 90 patients from the government clinics and 91 patients from private clinics. The majority of the patients were males (62.4%), Malay (79.0%), aged between 25 to 34 years with a mean age of 34.6 years and acutely ill (80.7%). Generally, all patients were satisfied with the services provided in both government and private sectors. Patients in private clinics, however, had a significantly higher satisfaction score as compared to the respondents in government clinics. There was significant correlation between patient satisfaction score and household income in government and private clinics. Significant con·elation was also found between patient satisfaction score and age in government clinic. Patients in private clinics were more satisfied towards the interpersonal manners, availability and continuity of care of the clinic compared to patients in government clinics. Whereas patients in government clinics were more satisfied towards the service charges. This study provides important information that could be used by providers of health care services to monitor and improved the quality of medical care in the respective sectors.